The effect of diets supplemented with Coriandrum sativum seeds on carcass performance, immune system, blood metabolites, rumen parameters and meat quality of lambs - Hassan Khamisabadi; Javad Ahmadpanah (Acta Scientiarum. Animal Sciences, 2020)
A trial was conducted to investigate the effects of dietary Coriandrum sativum seeds on carcass performance, immune system, blood metabolites, rumen parameters and meat quality of Lambs. 16 Sanjabi lambs of 27 ± 5.1 kg during post-weaning (97 d of age) period were randomly selected. Four diets including 0, 1, 3, and 5% coriander seeds, replaced by Alfa alfa in the diet, were considered. A 30:70 alfalfa hay: concentrate diet for a period of time (97 to 187 d of age) was used. The results showed that feed intake was significantly increased by adding coriander seeds, linearly. There was no significant difference for apparent digestibility of crude protein, crude fat, neutral and acidic detergent fiber, crude ash, rumen fluid pH and ammonia nitrogen at 0, 2 and 4 h after feeding, Meat dry matter, ash, crude protein and fat, and the meat’s fatty acid profile (p > 0.05). Dietary coriander seeds had a significant effect on neutrophils, lymphocytes, monocytes and eosinophil’s (in days 7 and 14 of trial) and blood metabolites at the middle of trial. Obtained results suggested that supplementation of coriander seed may have limited effects on nutrient digestibility, ruminal parameters, meat quality, blood cells and metabolites.